KUALITAS SEMEN CAIR SAPI SIMENTAL MENGGUNAKAN LARUTAN ISOTONIS KOMERSIAL PADA KONSENTRASI DAN LAMA PENYIMPANAN BERBEDA - Bayu Anke Mardian; Zumarni Zumarni; Anwar Effendi Harahap (State Islamic University of Sultan Syarif Kasim Riau, 2017)
Artificial insemination (AI) is a technique to insert the sperm or semen of bull thawed and processed first into the genital tract of female methods and a special tool called insemination gun, efforts to optimize the management of the cement in order to obtain the quality of cement is optimal to do with the selection of diluent cement. One alternative materials cement diluent is an isotonic solution Commercial (LIK). This study aimed to examine the interaction between the concentration and duration of storage of diluent solution isotonic different to the quality of spermatozoa cow simental. This research was conducted at the Regional Technical Implementation Unit of Artificial Insemination Centres (UPTD BIB) Tuah Sakato, Payakumbuh. In April 2016. This study used a randomized block design (RAK) factorial design to Factor A (Concentration LIK) ie A1 = 100 ml Tris Egg Yolk, A2 = (60 ml) Tris Egg Yolk + (40 ml) LIK, A3 = (55 ml) Tris Egg Yolk + (45 ml) LIK, A4 = (50 ml) Tris Egg Yolk + (50 ml) LIK, and factor B (retention) is B1 = 0 day, B2 = 1, B3 = 2 day, days, B4 = 3 days. Each treatment consists of three replicates. Parameters measured were motility, percentage of survival, abrnormalitas, and MPU. These results indicate that an isotonic solution can be used as an alternative Commercial diluent with the best results on the percentage LIK 40 ml, but the effectiveness of the efficiency of storage use was only on the first day (24 hours).